(untitled) (World Bulletin of Social Sciences, 2025)
In the modern digital society, artificial intelligence technologies, particularly deepfakes, have become not only creative tools but also means of committing crimes. This paper examines the main types of crimes associated with the use of deepfakes, including the dissemination of defamatory materials, fraud, invasion of privacy, and political manipulation. Special attention is given to the methods of detecting and investigating such offenses. The study analyzes current deepfake detection algorithms, forensic video and computer-technical examination techniques, as well as issues of legal regulation and international cooperation in this field. The problems of identifying the sources of fake content and collecting digital evidence are highlighted. The conclusion emphasizes the need for a comprehensive approach combining technical, legal, and forensic methods to effectively counter crimes based on the use of deepfake technologies